1995
DOI: 10.1093/jmedent/32.2.143
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Development of Ixodes scapularis (Acari: Ixodidae) Under Various Climatic Conditions in Ontario, Canada

Abstract: Distribution of the blacklegged tick, Ixodes scapularis Say, is poorly defined in Ontario. An endemic population is known on Long Point peninsula, Lake Erie, Ontario, but I. scapularis adults have also been collected from other localities within the province. To test the hypothesis that distribution of the blacklegged tick is limited by cold climatic extremes, 35 fed female, 70 unfed adult, and 70 unfed nymphal I. scapularis were held in containers within four natural habitats on Long Point (42 degrees 36' N; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
118
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(123 citation statements)
references
References 19 publications
5
118
0
Order By: Relevance
“…In our overwinter experiment, we observed that when warm weather melted the snow cover in February, overwinter survival dropped to 33%. Our findings are consistent with other researchers who found that overwinter survival of I. scapularis females at Long Point, Ontario decreased due to lack of snow cover [21]. As well, Brunner et al found that blacklegged ticks are sensitive to cold threshold temperatures [22].…”
Section: Snow Coversupporting
confidence: 93%
“…In our overwinter experiment, we observed that when warm weather melted the snow cover in February, overwinter survival dropped to 33%. Our findings are consistent with other researchers who found that overwinter survival of I. scapularis females at Long Point, Ontario decreased due to lack of snow cover [21]. As well, Brunner et al found that blacklegged ticks are sensitive to cold threshold temperatures [22].…”
Section: Snow Coversupporting
confidence: 93%
“…Extreme winter temperatures can limit the northern distribution of ticks by directly killing the ticks, 43,50 inhibiting host-seeking activity, 44,46,47 or limiting the availability of hosts. 51 The high rate of fall cooling can also affect tick population dynamics by limiting the time available for larvae to find a host in the fall, thus entering diapause unfed, 52 which potentially increases their mortality rate. 52 On the other hand, high rates of spring warming may have an opposite effect, because it would result in faster accumulation of degree-days for development, potentially leading to earlier egg deposition and larval emergence.…”
Section: Discussionmentioning
confidence: 99%
“…Winter survival depends on minimum temperatures, duration of exposure to cold, the tick's developmental stage and feeding status. Even if the tick survives the winter, further ability to undergo metamorphosis the following spring depends on the length and magnitude of exposure to the cold (Lindsay et al, 1995). Nymphs and adults may resist freezing temperatures well below -7 ºC, whereas eggs and larvae, especially if fed, are slightly more sensitive to the cold (Table 4) (Balashov, 1972;Daniel et al, 1977;Gray, 1981).…”
Section: Climate and The Life-cycle Dynamics Of The Tickmentioning
confidence: 99%